Tailoring the physicochemical properties of core-crosslinked polymeric micelles for pharmaceutical applications - Hu, Qizhi; Rijcken, Cristianne J F; van Gaal, Ethlinn; Brundel, Paul; Kostkova, Hana; Etrych, Tomas; Weber, Benjamin; Barz, Matthias; Kiessling, Fabian; Prakash, Jai; Storm, Gert; Hennink, Wim E; et al. (Journal of controlled release, 2016)
To optimally exploit the potential of (tumor-) targeted nanomedicines, platform technologies are needed in which physicochemical and pharmaceutical properties can be tailored according to specific medical needs and applications. We here systematically customized the properties of core-crosslinked polymeric micelles (CCPM). The micelles were based on mPEG-b-pHPMAmLacn (i.e. methoxy poly(ethylene glycol)-b-poly[N-(2-hydroxypropyl) methacrylamide-lactate]), similar to the block copolymer composition employed in CriPec® docetaxel, which is currently in phase I clinical trials. The CCPM platform was tailored with regard to size (30 to 100nm), nanocarrier degradation (1month to 1year) and drug release kinetics (10 to 90% in 1week). This was achieved by modulating the molecular weight of the block copolymer, the type and density of the crosslinking agent, and the hydrolytic sensitivity of the drug linkage, respectively. The high flexibility of CCPM facilitates the development of nanomedicinal products for specific therapeutic applications.
Keywords: Doxorubicin; Nanomedicine; docetaxel; akrylamidy; Micelles; Drug Carriers; Polymers; Drug release; Docetaxel; Drug Liberation; Cross-Linking Reagents; Taxoids; Core-crosslinking; reagencia zkříženě vázaná; Polymeric micelles; molekulová hmotnost; Acrylamides; doxorubicin; micely; polymery; nosiče léků; uvolňování léčiv; Molecular Weight; taxoidy; Drug targeting